Depictions of deities on the kumbha (pot) mouldings - Temples of India Project Team (Jio Institute, 2024)
Seen here is the exterior of the southern shrine in the Neelkanth Mahadev triple-shrine temple. The walls of the shrine have fallen, leaving only the plinth up to the level of the kumbha (pot) molding in situ. Few traces of the kalasha (pitcher) moulding above the kumbha have survived. The faces of the kumbha molding have depictions of various deities. The central kumbha corresponding to the main bhadra (central projection) of the temple has Vishnu Lakshmi on Garuda.